METHODICAL APPROACH TO AN ASSESSMENT OF A LEVEL OF QUALITY AND COMPETITIVENESS OF GOODS - N. Zemlyanskaya; N. Kazakova; M. Cherkasov (Вестник университета)
In the article it is proved that marketing is one of the most effective mechanisms of regulation of a level of quality and competitiveness of production. It is offered to estimate a level of quality and competitiveness by means of indicators of norm and mass of potrebitelny cost of goods. Possible approaches to definition of these indicators are shown.